Pharmacological interventions for the treatment of bleeding in people treated for blunt force or penetrating injury in an emergency department: a systematic review and network meta-analysis (Protocol) - Erasu, V; Novak, A; Gibbs, VN; Champaneria, R; Dorée, C; Hafeez, A; Moy, R; Sandercock, J; Brunskill, SJ; Estcourt, LJ (Cochrane Collaboration, 2022)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows: To systematically review the optimal administration and relative efficacy of pharmacological interventions for preventing blood loss in people treated in an emergency department for bleeding caused by a blunt force or penetrating injury.